Psoriatic arthritis - Tofacitinib as a new treatment - Skorupska, Marta; Czeczotka, Magdalena Joanna; Martka, Martyna Magdalena; Popławska, Natalia Aleksandra; Śliz, Justyna; Woźniak, Krzysztof (Journal of Education, Health and Sport, 2024)
Introduction: JAK inhibitors are used in the treatment of psoriatic arthritis when there is a lack of effective response or intolerance to first-line drugs or their use must be discontinued due to the presence of side effects. JAK inhibitors inhibit the JAK-STAT signaling pathway which plays a significant role in the pathogenesis of many inflammatory and autoimmune diseases. This mechanism leads to a reduction in the level of pro-inflammatory cytokines which causes rapid improvement in the patient's clinical condition. Tofacitinib is the best-known drug in this group; its use carries an increased risk of cardiovascular events and reactivation of the varicella-zoster virus. Regular monitoring of patients results in faster detection of the first signs of undesirable effects and the cessation of their progression. The drug's safety profile is acceptable and the benefits outweigh possible complications. Aim of the study: The aim of the study is to summarize the available knowledge about tofacitinib treatment in psoriatic arthritis. The way of work, effectiveness of treatment and potential side effects were summarized and described. Materials and methods: The literature available in PubMed database was reviewed using the following keywords: “Psoriatic arthritis”, “Tofacitinib”, “JAK inhibitors”, “JAK-STAT” Conclusion: Tofacitinib treatment in rheumatology is used in psoriatic arthritis. The rapid improvement in the clinical condition of patients treated with JAK inhibitors is due to their direct impact on the modulation of the pathogenesis of the disease. The predictable benefits of therapy outweigh the side effects which can be detected at an early stage with regular monitoring of the patient.